The Current Strategies for Neoadjuvant Chemotherapy in Muscle Invasive Bladder Cancer: The Place of Immunotherapy in Future - (:unkn) unknown (GALENOS YAYINCILIK, 2020)
Muscle invasion is present in approximately thirty percent of bladder cancers. Radical cystectomy and bilateral pelvic lymph node dissection following neoadjuvant chemotherapy is the recommended treatment for muscle invasive bladder cancer. Local and distant relapses are seen in a significant proportion of patients with surgery alone. Micrometastases at the time of diagnosis that cannot be detected by imaging may be responsible for these relapses. The aim of neoadjuvant and adjuvant therapies is to eliminate these micrometastases. Several randomized trials have shown that platinum-based combination neoadjuvant chemotherapy can improve survival outcomes, compared with locoregional treatment alone. Although the proportion of patients receiving treatment has increased compared to previous years, it is still low. Immunotherapies in neoadjuvant treatment are promising in the appropriate patient group. In this article, we aimed to review current neoadjuvant treatment strategies in muscle invasive bladder cancer in the literature.
Keywords: Bladder cancer; chemotherapy; neoadjuvant therapy; TRANSITIONAL CELL-CARCINOMA; PHASE-III TRIAL; RADICAL CYSTECTOMY; CISPLATIN; METHOTREXATE; VINBLASTINE; DOXORUBICIN; MULTICENTER; CARBOPLATIN; GEMCITABINE